Fortified balanced energy-protein supplementation, maternal anemia, and gestational weight gain: A randomized controlled efficacy trial among pregnant women in rural Burkina Faso - Hanley-Cook, Giles T.; Toe, Laeticia Celine; Tesfamariam, Kokeb; de Kok, Brenda; Argaw, Alemayehu; Compaore, Anderson; Huybregts, Lieven (Elsevier, 2022)
Background; Anemia and suboptimal gestational weight gain (GWG) are associated with adverse maternal and birth outcomes. Limited research indicates that balanced energy-protein (BEP) supplements reduce the incidence of inadequate GWG. Objectives: We assessed the efficacy of a micronutrient fortified BEP supplement on the secondary outcomes: anemia, GWG, GWG rate, and GWG in relation to the IOM's recommendations, as compared to an iron-folic acid (IFA) tablet.